Cyclic behavior of RT-cement treated marine clay subjected to low and high loading frequencies - Al-Bared, M.A.M. (Techno-Press, 2020)
The weakening and softening behavior of soft clay subjected to cyclic loading due to the build-up of excess pore water pressure is well-known. During the design stage of the foundation of highways and coastal high-rise buildings, it is important to study the mechanical behavior of marine soils under cyclic loading as they undergo greater settlement during cyclic loading than under static loading. Therefore, this research evaluates the cyclic stress-strain and shear strength of untreated and treated marine clay under the effects of wind, earthquake, and traffic loadings. A series of laboratory stress-controlled cyclic triaxial tests have been conducted on both untreated and treated marine clay using different effective confining pressures and a frequency of 0.5 and 1.0 Hz. In addition, treated samples were cured for 28 and 90 days and tested under a frequency of 2.0 Hz. The results revealed significant differences in the performance of treated marine clay samples than that of untreated samples under cyclic loading. The treated marine clay samples were able to stand up to 2000 loading cycles before failure, while untreated marine clay samples could not stand few loading cycles. The untreated marine clay displayed a higher permanent axial strain rate under cyclic loading than the treated clay due to the existence of new cementing compounds after the treatment with recycled tiles and low amount (2) of cement. The effect of the effective confining pressure was found to be significant on untreated marine clay while its effect was not crucial for the treated samples cured for 90 days. Treated samples cured for 90 days performed better under cyclic loading than the ones cured for 28 days and this is due to the higher amount of cementitious compounds formed with time. The highest deformation was found at 0.5 Hz, which cannot be considered as a critical frequency since smaller frequencies were not used. Therefore, it is recommended to consider testing the treated marine clay using smaller frequencies than 0.5 Hz. Â© 2020 Techno-Press, Ltd.